Carbon Material With Ordered Sub-Nanometer Hole Defects - Liang, Nianjie; Li, Qiaosheng; Pan, Ganghuo; Liu, Chunxiang; Liu, Yuzhou (Frontiers in Chemistry, 2022)
A holey carbon material with ordered sub-nanometer hole defects was synthesized from oxidative cyclodehydrogenation of a polyhexaphenylbenzene precursor. It showed easy dispersion in a wide range of solvents, surprisingly including water. Band gap of around 2.2 eV is formed due to the narrow connection between the hexabenzocoronene subunits. This new carbon material was then proved as effective support for various inorganic nanoparticles of small sizes. The supported iron nanoparticles showed enzyme-like catalysis behavior in nitrophenyl reduction reaction by NaBH4, exemplifying the great potential of this new material in catalysis.